Influence of various factors on productivity of distillation column in distillation process of oil - Amerkhanova, Sh.K.; Shlyapov, R.M.; Uali, A.S. (Изд-во КарГУ, 2013)
It is obtained the generalized equation, reflecting the influence of each factor on the output fractions. The optimum parameters of the distillation process are established. It is revealed that increasing the flow rate lead to increase of the rate constants. The results of IR spectral studies show that all fractions of gasoline contain large amounts of saturated alkyl, unsaturated and aromatic compounds.
Keywords: oil; distillation process; distillation column; gasoline; IR spectral study; kinetics; rate constants; alkyl and unsaturated compounds; series of aromatic compounds